2013
DOI: 10.1063/1.4790884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave plasma treatment on silicon dioxide films grown by atomic layer deposition at low temperature

Abstract: The effects of microwave plasma treatments on the physical and electrical characteristics of silicon dioxide films are discussed. Plasma treatments significantly improve the characteristics at low temperatures. Differences in the type of inert gas, O2 partial pressure, and total pressure cause differences in the plasma energy and active species concentrations, which affect reduction in the impurity concentrations, generation of dangling bonds, and effective working depth of the plasma. The changes in the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…18 This is further enhanced by SPA plasma, which helps to produce a densification of dielectric films with smoother interface. 4,19 Furthermore, it is believed that thin GeO x -type interfacial layer is formed. Therefore, with the addition of Zr in HfO 2 from 0% to 75%, an increase in the accumulation capacitance ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 This is further enhanced by SPA plasma, which helps to produce a densification of dielectric films with smoother interface. 4,19 Furthermore, it is believed that thin GeO x -type interfacial layer is formed. Therefore, with the addition of Zr in HfO 2 from 0% to 75%, an increase in the accumulation capacitance ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, SPAO plasma enhances the formation of atomically flat and smoother dielectric surfaces and interfaces. 12,13,18,19 Impact of Zr incorporation on EOT, Flat-band voltage shift, and leakage current density.- Figure 6 shows the impact of Zr incorporation in HfO 2 on EOT, flat-band voltage (Fig. 6a), and gate leakage current density (Fig.…”
Section: 10mentioning
confidence: 99%
“…1 Recently, the effects of treatments using active oxygen species generated by the thermal decomposition of O 3 molecules or microwave excitation plasma have been investigated. [1][2][3] We also reported that the treatments using active oxygen species generated by Ar/O 2 plasma excited by the microwave is extremely effective. 4 We clarified that the mass density of the CVD-SiO 2 film is increased and the carrier trap density of the film is decreased by the Ar/O 2 plasma treatment with X-Ray Reflectivity (XRR) analysis and X-ray Photoelectron Spectroscopy (XPS) time-dependent measurement.…”
Section: Introductionmentioning
confidence: 94%
“…The metastable excitation energy of the Ar atom is lower than the ionization energy of the O 2 molecule or O atom. In contrast, the metastable excitation energy of the helium atom (He) is higher than the ionization energy of the O2 molecule or O atom. Although the Ar* atom does not ionize the O 2 molecule or O atom, the metastable excited state helium atom (He*) ionizes the O 2 molecule or O atom.…”
mentioning
confidence: 91%
“…6 The low electron temperature (<1 eV) of this plasma source and the separated plasma generation and process regions make it advantageous to enhance the oxide quality by exposing the dielectric during or after deposition. 7,8 The addition of Zr into HfO 2 was found to enhance the drain current with a reduced threshold voltage shift under positive bias temperature instability (PBTI) stress. 9 On the other hand, the addition of Zr and SPA plasma exposure does not cause any interface degradation, as dielectrics are not subjected to any post deposition annealing.…”
mentioning
confidence: 99%